Acute, Subchronic, and Chronic Complications of Radical Prostatectomy Versus Radiotherapy With Hormone Therapy in Older Adults With High-Risk Prostate Adenocarcinoma - Wu, Szu-Yuan; Huy, Le Duc; Liao, Chih Jung; Huang, Chung-Chien (Frontiers in Oncology, 2022)
Purpose: To compare acute, subchronic, and chronic complications between older patients with high-risk localized prostate cancer (HR-LPC) receiving radical prostatectomy (RP) and high-dose intensity-modulated radiotherapy (IMRT) combined with long-term hormone therapy (HT). Patients and Methods: We recruited older patients (≥80 years) with HR-LPC from the Taiwan Cancer Registry database. After propensity score matching, logistic regression analysis was used to compare the acute, subchronic, and chronic complication rates between patients who underwent RP (the RP group) and high-dose IMRT combined with long-term HT (the IMRT+HT group). Results: Benign prostatic hyperplasia (BPH) symptoms and urinary incontinence (UI) were the most common complications over 5 years (BPH symptoms: RP, 17.69%; IMRT+HT, 29.58%; UI: RP, 10.47%; IMRT+HT, 5.50%). Compared with the RP group, the IMRT+HT group had higher odds of BPH symptoms and lower odds of UI and hernia after the 5-year follow-up period. The impotence rates were significantly higher in the IMRT+HT group than in the RP group at 3 months and 1 year after treatment and became nonsignificant after 2 years. At 5 years after treatment, the IMRT+HT group had lower risks of UI (adjusted odds ratio [aOR], 0.50; 95% confidence interval [CI], 0.28–0.88) and hernia (aOR, 0.21; 95% CI, 0.11–0.82) and a higher risk of BPH symptoms (aOR, 4.15; 95% CI, 2.82–7.37) than the RP group. Conclusion: IMRT+HT was associated with lower UI and hernia risks than RP. By contrast, RP was associated with fewer complications of BPH over the follow-up period and less impotence during the first year after treatment. Our findings provide important and valuable references for shared decision-making for optimal therapy selection among older men with HR-LPC.